Edukacja klimatyczna w podstawie programowej: wyzerowany program Elliota Eisnera - Kozłowska, Agnieszka (Wydawnictwo Naukowe UAM, 2023)
Badanie podstawy programowej dla szkół ponadpodstawowych wykazało marginalną obecność w niej tematyki klimatycznej. Pojęcie zmiana klimatu pojawia się w całym dokumencie cztery razy na rozszerzonej geografii, a pomijane są aspekty etyczne, społeczne, humanistyczne. Retoryka tych zapisów oscyluje między denializmem klimatycznym (zaprzeczeniem istnienia problemu) a adaptacją (odpowiedź na zagrożenia). Spośród 100 słów kluczowych charakteryzujących zmianę klimatu z perspektywy nie tylko przyrodniczej, ale także społecznej, w dokumencie wystąpiło tylko sześć. Jest to podstawą uznania edukacji klimatycznej i jej transdyscyplinarnego charakteru za wyzerowany program Elliota Eisnera. Ta luka czyni młodzież bardziej podatną na denializm klimatyczny i dezinformację klimatyczną, zmniejsza jej szanse w zetknięciu się ze skutkami kryzysu klimatycznego i na przeciwdziałanie temu zjawisku. Sytuację może zmienić edukacja, traktująca zmianę klimatu holistycznie i wielowymiarowo, podejmująca nie tylko przyrodnicze, ale także psychologiczne, społeczne, filozoficzne, językowe, etyczne i historyczne wątki związane z tym tematem. Climate change is one of humanity’s greatest challenges, and education is an important tool for combating it. However, despite obligations stemming directly or indirectly from international agree ments, climate education is primarily provided outside the formal education system. This study aimed to investigate the presence and scope of climate education content, as well as the narrative of the environmental and climate crisis, in the core curriculum for secondary schools. Document analysis (content analysis) was used as the research method, according to a customized key compris ing 100 keywords across 9 categories. The material subjected to the study was the core curriculum for post-primary schools (secondary schools, technical schools, and upper secondary vocational schools). All subjects of the core curriculum were included in the analysis, as climate change is re lated to not only natural sciences but also social sciences and humanities. The results of the analysis revealed the marginal presence of climate education in the core curriculum. The expression climate change appears only 4 times in the entire document, in one subject: geography. Out of the 100 codes describing the climate and environmental crisis, only 6 appeared in the document: climate change, sustainability, biodiversity, environmental disastermaintaining balance, and deforestation. These terms occurred in a context that was characterized by a narrative of skepticism about human respon sibility for the current state of the environment and the potential risks of continuing to overexploit the planet. Conclusions: The current approach to climate education foisters a false, denialist envi ronmental consciousness based on the belief “nothing is happening, everything is under control”. It fails to equip students with the necessary skills to address climate change and the environmental crisis. Thus, it can be considered as a null curriculum of Elliot Eisner.
Climate education in core curriculum: A null curriculum of Elliot Eisner
Keywords: zmiana klimatu; edukacja klimatyczna; kryzys ekologiczny; podstawa programowa; wyzerowany program; Elliot Eisner; climate change; climate education; environmental crisis; climate crisis; core curriculum; secondary school; null curriculum